Hypothesis Testing on Regression: Investigating Students’ Skill - Abdol Razak, Fadzilah; Rashidah, Nor; Baharun, Norhayati; Afni Deraman, Noor (International Journal of Engineering and Technology, 2018)
This study aims to investigate students’ ability to write a correct hypothesis based on the statement referring to regression coefficients.  Different statements of regression coefficients, specifically the slope were given in the standard format of test questions and the students were asked to conduct an appropriate hypothesis test. From the decision made, the students also had to provide suitable conclusions on each of the tests conducted. 197 answer scripts were inspected and the focus was given to the hypothesis statement and the conclusion provided by the students. The results indicated that students were able to write proper hypothesis statement for a regression coefficient that directly refers to the slope of the variable. However, they failed to provide correct hypothesis when they had to translate the definition of slope to an appropriate hypothesis statement. Despite their ability to write simple hypothesis for regression slope, they still had difficulties in providing conclusions for the tests conducted. The study also clearly revealed that even though some of the students managed to write proper conclusions, they did not correspond to the hypothesis statements given earlier, as the conclusions made were merely based on the question statement.